2006
DOI: 10.1080/14634980500536030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by fermentation: Review of a new approach to environmentally safe energy production

Abstract: As a new clean energy source, the demands for and use of hydrogen fuel are rapidly increasing. Therefore, biohydrogen production technology is being developed to reduce operation costs in many countries. Improvement of biohydrogen production capacity and cost reduction are key factors to bring about industrial implementation. One of the most effective production methods is microbiological: the use of bacteria with high hydrogen-production capacity and performance. The anaerobic process of biohydrogen productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…In a review of their work, Ren et al [23] gave the optimal operating conditions for the ethanol/acetate hydrogen-producing fermentation of molasses as pH 4.0-4.5, HRT 4-6 h. Ren et al [62] reported continuous hydrogen production with ethanol and acetate production at pH around 4.5 from CSTR experiments with a mixed culture and molasses at 30 • C, whilst no gas was produced at pH 4.9. They claim propionic acid fermentation is dominant in the pH range 5-6.…”
Section: Process Ph and Hrtmentioning
confidence: 97%
See 1 more Smart Citation
“…In a review of their work, Ren et al [23] gave the optimal operating conditions for the ethanol/acetate hydrogen-producing fermentation of molasses as pH 4.0-4.5, HRT 4-6 h. Ren et al [62] reported continuous hydrogen production with ethanol and acetate production at pH around 4.5 from CSTR experiments with a mixed culture and molasses at 30 • C, whilst no gas was produced at pH 4.9. They claim propionic acid fermentation is dominant in the pH range 5-6.…”
Section: Process Ph and Hrtmentioning
confidence: 97%
“…Further work is thus needed to clarify the nature and usefulness of the relationship of B/A ratio to molar hydrogen yield. Although production of the reduced end product ethanol from hexose consumes NADH, Ren's group has shown that a fermentation producing ethanol and acetate from carbohydrate in a molar ratio close to 1 is favourable for hydrogen production [22,23]. The reactor, with flocculant sludge at pH 4.5 (approx.)…”
Section: Microbiology and Biochemistry Of Dark Fermentative Hydrogen mentioning
confidence: 99%
“…The effect of pH is known to be crucial due to its effects on hydrogenase activity, metabolism pathways, and microbial communities . The microbial community is very important parameter for the success in biological hydrogen production process and is the key factor to bring sustainable biohydrogen production and industrial implementation (Iyer et al 2004;Ren et al 2006). This work focused on the statistical optimization of physico-chemical parameters (pH, temperature) in cultural conditions for biohydrogen production from palm oil mill effluent (POME) in batch and continuous reactor, their interaction on hydrogen production, long-term evaluation of optimization condition and investigated the responsible microbial community using PCR-DGGE technique.…”
Section: Introductionmentioning
confidence: 99%
“…In these reactions, organic compounds of food waste are electron donors, and О 2 , NO 3 -, SO 4 2-, H + , and CO 2 are acceptors. Microorganisms act as a biocatalyst in the donor-acceptor reaction (Noike and Mizuno, 2000;Hawkes et al, 2002;Kapdan and Kargi, 2006;Ren et al, 2006). The rate and efficiency of microbial degradation of organic compounds in general and food waste in particular are determined by the release of free energy ΔG in the coupled donor-acceptor reaction (Finley et al, 2009;Bethke et al, 2011).…”
Section: Resultsmentioning
confidence: 99%